UJI DAYA HAMBAT ISOLAT Actinomycetes SEBAGAI ANTIBAKTERI TERHADAP PERTUMBUHAN Pseudomonas aeruginosa ATCC27853 SECARA IN VITRO - Saskia Arientika Wahyuningrum (2020)
Pneumonia is a lung parenchymal infection caused by Pseudomonas aeruginosa. P.aeruginosa is Gram negative bacteria that has developed antibiotic resistance. Actinomycetes are Gram positive bacteria that produces secondary metabolites which have the ability as antimicroba. This study aims to see the ability of Actinomycetes isolates to inhibit the growth of the bacterium Pseudomonas aeruginosa ATCC 27853. The samples in this experiment are from Kebun Raya Bogor that had been rejuvenated on Strach Casein Agar (SCA). Six dilution series 10-1; 10-2; 10-3; 10-4; 10-5; 10-6 Actinomycetes isolates were used to observe the inhibition zone of P.aeruginosa growth on Mueller Hinton Agar (MHA) media by diffusion method. The effective incubation time occurred at 24 hours, then it resulted in the average clear zone diameter of 14.70mm, 10.57 mm, 8.53 mm, 8.47 mm, 6.97 mm, and 5.30 mm. The results of the One -Way ANOVA test with p value =0.000 (p < 0.005) showed some differences at each concentration to inhibit the growth of P.aeruginosa ATCC 27853 at 24 hours incubation period. The antibacterial mechanism produced from secondary metabolite compounds of Actinomycetes isolates would be able to change the permeability of the cell walls, thus causing shrinkage and wrinkage in Gram negative bacteria.